The Demand of Tobacco Consumption in West Sumatra - Yollit Permata Sari; Isra Yeni; Melti Roza Adry; Dewi Zaini Putri; Urmatul Uska Akbar (Muhammadiyah University Press, 2021)
This study uses two estimation models, logistic and linear regression. The logit model is used to see the probability of an individual being a tobacco user. The second method uses multiple linear regres- sion which aims to see the factors that influence the demand for tobacco consumption in West Suma- tra. This research was obtained from National Socio-Economic Survey in 2019. Comparing these two models, there was a slight difference. Income does not influence an individual’s decision to become a tobacco user, while this variable is significant in influencing the demand for tobacco. This study also reveal that social and economic factors are significant in influencing the demand for tobacco in West Sumatra. Economic factors show that tobacco is a normal good. Meanwhile, from social factors such as education level shows that the lower the level of education causes individuals to become tobacco users and also causes the demand for cigarettes in West Sumatra to increase. This result causes the standard of household living to be disrupted because education is a human capital investment. So that various policies from the government are expected to control tobacco consumption in West Sumatra.